Perfect 3-Colorings of The Petersen‎ Graph - Mehdi Alaeiyan; Hamed Karami; Sajjad Siasat (IndoMS, 2018)
‎In this paper we enumerate the parameter matrices of all perfect 3-colorings of the Petersen graph‎.